Taxonomia, ecologia e distribuição espacial de rotifera no estado de São Paulo - Ribeiro, Tainá Alves (2019)
Rotifers inhabit a variety of aquatic habitats. It is thought that the success of this group is largely due to their small size, short life cycle, ang high richness of species, being these aspects largely responsible for the species richness of zooplankton communities in freshwater ecosystems. The aim of this study was to evaluate the taxonomic composition of rotifer communities in different types of freshwaters of São Paulo state, distributed in 22 Management unities of water resources (UGHRI). Zooplankton communities of 283 water bodies were sampled by horizontal net hauls. In situ measurements of pH, electrical conductivity, temperature and O2 concentrations were performed and water samples were simultaneously taken for laboratory measurements of chlorophyll a concentration. Based on chlorophyll concentration values, the trophic state index (TSI) was calculated and water bodies were then classified in one of six categories regarding their trophic degree. A total of 113 species of Rotifera, belonging to 20 different families were recorded. Families with highest species richness were Lecanidae, Brachionidae and Trichocercidae, following a pattern already described for tropical region rotifer communities. The species with highest frequency of occurrence were Lecane bulla, ocurring on 70% of all water bodies sampled and Lecane leontina, with 35,9%. There was a significant linear relationship between the number of water bodies sampled in each management unity and their rotifer species richness. It was also verified a low positive correlation, but statistically significant between species richness and the trophic state of the water bodies. There were evidences that the spatial distribution pattern observed for rotifers was influenced mainly by physical and chemical characteristics and trophic state of the water bodies. There are indicatives that differently from the pattern frequently observed for microorganisms, the distribution of most species can be restricted more by tolerance limits regarding environmental variables than by their dispersal capacity.